1997
DOI: 10.1136/vr.140.22.577
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of the red poultry mite to pyrethroids in France

Abstract: The resistance of Dermanyssus gallinae, the red poultry mite, to a pyrethroid acaricide, permethrin, and to an organophosphate, dichlorvos, was examined on five French poultry farms which had experienced problems in controlling mite populations and on one farm with no problems. The concentration of permethrin required to kill 50 per cent of the mites on the five farms was between eight and 40 times the concentration required on the control farm. In contrast, no resistance to dichlorvos was detected. This is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 8 publications
2
74
0
Order By: Relevance
“…In addition to the detection of viruses or bacteria in poultry red mites, these molecular methods would also lead to progress in the knowledge of their genetics: population genetics, gene transmission, pseudo arrhenotoky, mechanisms that are involved in the development of acaricide resistance [3,18]. All these studies require DNA and therefore the development of an efficient extraction protocol.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the detection of viruses or bacteria in poultry red mites, these molecular methods would also lead to progress in the knowledge of their genetics: population genetics, gene transmission, pseudo arrhenotoky, mechanisms that are involved in the development of acaricide resistance [3,18]. All these studies require DNA and therefore the development of an efficient extraction protocol.…”
Section: Introductionmentioning
confidence: 99%
“…In France, reports show an endemic situation with almost all part of the country showing infestations (Beugnet et al 1997;Chauve 1998) with a higher prevalence during the winter (Lubac et al 2003) whereas in Denmark worst infestation cases are observed in the late summer (personal communication, Kilpinen, Lyngby, Denmark) and also in Italy (personal communication, Camarda, University of Bari, Italy).…”
mentioning
confidence: 99%
“…In addition, the environment and non-targeted organisms may be affected. Another consequence is the selection of pest populations resistant to specific chemical principles, as previously reported (Beugnet et al, 1997;ChernakiLeffer 2004;Lambkin, 2005). This situation may become even worse when the application of chemical insecticides is not associated with pest monitoring.…”
Section: Problems In Pest Control In Poultry Housesmentioning
confidence: 77%